Efeitos imunomoduladores da colostrinina sobre a atividade funcional de fagócitos presentes em sangue e colostro de mulheres com excesso de peso - Pereira, Elisia Possidônea (2019)
Chronic inflammation promoted by obesity can be aggravated during pregnancy by altering the immune system and metabolism, allowing complications for the health of both mother and child. Colostrin, a polypeptide found in colostrum, appears to play a key role in the development of the newborn's immune system. This study aims to evaluate the effects of colostrin on the functional activity of those present in the blood and colostrum of overweight women. The study was developed with maternal blood and colostrum measurements, considering the pre-gestational nutritional status (normal, overweight and obesity). Functional activity of cells was analyzed by fluorescence microscopy method, a superoxide nitrogen dosage performed by ferricitochrome C method, a Superoxide Dismutase (SOD) enzyme using the tetrazolium nitroazul reduction method and spectrophotometrically read. It also verified the intracellular Ca2 + release of colostrum MN phagocytes by flow cytometry. As a result, greater than 95% viability is achieved in all treatment groups and types. No blood, mood levels did not change between nutritional status and treatment type, but no colostrum was found to increase in the presence of colostrinin and bacteria. SOD release shows an increase in colostrum-treated cells relative to untreated or enteropathogenic Escherichia coli (EPEC) cells, compared to nutritional status. Colostrin also increased phagocytic activity in both blood and milk, but microbiological index increased only in colostrum phagocytes in overweight groups. Treatment of cells with colostrin reduces the release of calcium by colostrum MN phagocytes from overweight mothers. The results of the present study demonstrate that colostrinin was able to modulate the phagocytic and microbiological activity of human colostrum phagocytes in obesity and obesity groups, besides controlling or exerting oxidative stress.